Optimal and System Myopic Policies for Multi-Echelon Production/Inventory Assembly Systems - Schwarz, Leroy B.; Schrage, Linus (Management Science, 1975)
In this paper optimal and near optimal policies are proposed for multi-echelon production/inventory assembly systems under continuous review with constant demand over an infinite planning horizon. Costs at each stage consist of a fixed charge per order or production setup plus a linear holding cost on “echelon” inventory. The objective is minimization of average cost per unit time. The major results of this paper are: a mathematically simple, often optimal, “system myopic” solution, a lower bound on the closeness to optimality of this solution, and a branch and bound algorithm which usually finds the optimal solution quickly.